Ambient Intelligence - Jesus Villanueva Molina, Felix (IntechOpen, 2010)
It can no longer be ignored that Ambient Intelligence concepts are moving away from research labs demonstrators into our daily lives in a slow but continuous manner. However, we are still far from concluding that our living spaces are intelligent and are enhancing our living style. Ambient Intelligence has attracted much attention from multidisciplinary research areas and there are still open issues in most of them. In this book a selection of unsolved problems which are considered key for ambient intelligence to become a reality, is analyzed and studied in depth. Hopefully this book will provide the reader with a good idea about the current research lines in ambient intelligence, a good overview of existing works and identify potential solutions for each one of these problems.